Food microbiology : an introduction - Montville, Thomas J. (ASM Press, 2008)
This impressive second edition by Thomas Montville and Karl Matthews builds upon the earlier edition's success covering the complex field of food microbiology while also motivating students to venture beyond memorization to a broader understanding of the concepts. Organized into five major sections, which can be taught in any order, this new edition adds important new details, including expanded coverage of food fermentations.